2022
DOI: 10.28991/esj-2023-07-01-06
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and Stabilization of Aspergillus Fumigatus α-Amylase by Adsorption on a Chitin

Abstract: In this research, immobilization of A. fumigatus α-amylase on chitin was studied with the main purpose to improve the characteristics of the enzyme. A series of experiments were carried out to study stability improvement, thermodynamic parameters, include ki, ΔGi, and t½, and reusability of the immobilized enzyme. The experimental results indicate that significant thermal stability was achieved, as indicates by the ability of the enzyme to retain its relative activity above 39% after 80 min of incubation at 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…Oleh karena itu, pengembangan media seperti video, game, simulasi, maupun alat peraga lainnya sebaiknya menghadirkan contoh-contoh yang familiar dari kehidupan sehari-hari siswa untuk mempermudah pemahaman dan meningkatkan transfer konsep bagi siswa. Selain itu, media tersebut juga perlu dirancang untuk melatih keterampilan abad 21, seperti berpikir kritis, kreativitas, literasi teknologi, dan keterampilan komunikasi serta kolaborasi, sehingga sesuai dengan tuntutan era revolusi industri 4.0 saat ini (Irawan, 2023). Dengan demikian, para pendidik dan pengembang media pembelajaran perlu mempertimbangkan aktivitas dan konten edukasi yang secara eksplisit melibatkan siswa dalam pengembangan keterampilan abad ke-21 agar mereka dapat beradaptasi dan bersaing secara efektif di era digital saat ini dan masa depan.…”
Section: Gambar 1 Media Kertas Lipat Gambar 2 Media Papan Tulis Gamba...unclassified
“…Oleh karena itu, pengembangan media seperti video, game, simulasi, maupun alat peraga lainnya sebaiknya menghadirkan contoh-contoh yang familiar dari kehidupan sehari-hari siswa untuk mempermudah pemahaman dan meningkatkan transfer konsep bagi siswa. Selain itu, media tersebut juga perlu dirancang untuk melatih keterampilan abad 21, seperti berpikir kritis, kreativitas, literasi teknologi, dan keterampilan komunikasi serta kolaborasi, sehingga sesuai dengan tuntutan era revolusi industri 4.0 saat ini (Irawan, 2023). Dengan demikian, para pendidik dan pengembang media pembelajaran perlu mempertimbangkan aktivitas dan konten edukasi yang secara eksplisit melibatkan siswa dalam pengembangan keterampilan abad ke-21 agar mereka dapat beradaptasi dan bersaing secara efektif di era digital saat ini dan masa depan.…”
Section: Gambar 1 Media Kertas Lipat Gambar 2 Media Papan Tulis Gamba...unclassified
“…This is due to chitosan's unique property, which is that under acidic circumstances, the NH2 group in the linear chain changes to NH3 [43]. Acidic pH conditions can support the association of negatively charged enzyme groups with positively charged chitosan groups [44,45].…”
Section: Figure 5 Correlation Between Ph Variation and Adsorption Act...mentioning
confidence: 99%
“…The BET isotherm plot which indicates the nitrogen adsorption/desorption isotherms of the biochar gives a picture of the adsorption capacity of the biochar which is dependent on pore size and specific surface area. Several studies have shown that the degree of removal of heavy metal particulates or contaminants from aqueous solution is directly proportional to the pore size and specific surface area [81][82][83][84][85][86][87][88][89][90][91].…”
Section: Scanning Electron Microscopy (Sem) and Energy Dispersive X-r...mentioning
confidence: 99%
“…Spectra shift of the C=O group indicates cation exchange and can be a plausible mechanism for the removal of M 2+ from aqueous solution. Some authors [89,90] have implicated cation exchange, inner sphere complexation, coprecipitation, electrostatic interaction and hydrophobic 𝜋 − 𝜋 interaction as the mechanism for sorption of heavy metals using modified biochar.…”
Section: Mechanism Of Heavy Metals Adsorption Unto Modified Biocharmentioning
confidence: 99%
See 1 more Smart Citation